2020
DOI: 10.1177/1073274820954460
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictor of Cervical Cancer Screening Service Uptake Among Women Aged 25 Years and Above in Sidama Zone, Southern Ethiopia, Using Health Belief Model

Abstract: Cervical cancer is the fourth most common cancer affecting women worldwide, and the second leading cancer in Ethiopia. Screening gives protective benefits associated with a reduction in the incidence of invasive cervical cancer and mortality. However, the level of cervical cancer screening uptake is not well document in the country. This study aimed to determine the prevalence and predictors of cervical cancer screening service uptake among women aged 25 years and above in Sidama zone, southern Ethiopia, 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…It is also possible that including additional patient information could lead to better performance. Variables such as income and education levels have been found to be good predictors of attendance for cervical cancer screening [54,55]. However, our aim was to leverage routinely available data to inform patient prioritization by SDS.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…It is also possible that including additional patient information could lead to better performance. Variables such as income and education levels have been found to be good predictors of attendance for cervical cancer screening [54,55]. However, our aim was to leverage routinely available data to inform patient prioritization by SDS.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Among all eligible women, receiving notification had a significant effect on their attendance and participation willingness. This may be because, as the first step in organized two-cancer screening, notification serves as the cue or trigger to action two-cancer screening [ 31 , 32 ]. Furthermore, the proportion of community leaders as screening notifiers was significantly higher than that of those of GPs, which would reflect the nature of the public service of organized two-cancer screening, and the functions and importance of community leaders in providing public services and managing public affairs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, perceived susceptibility was associated with higher uptake rates in Ghana [ 55 ], Ethiopia [ 39 ] and Iran [ 56 ]. Additionally, higher perceived benefits were found to encourage screening behaviours in Nepal [ 41 ], Ghana [ 55 ] and Ethiopia [ 57 ]. In a recent review, Simbar et al [ 58 ] concluded that training-based interventions are able to modify perceived susceptibility and benefits, leading to behavioural changes.…”
Section: Discussionmentioning
confidence: 99%